Chemist at work in Dow Agricultural Research and Development Laboratory - Dow Chemical Company (1952)
General view of an unidentified employee at work in the Dow Chemical Company's Agricultural Chemical Research and Development Laboratory, with view of assorted laboratory equipment and apparatus. Per an article in the August 1941 edition of the Dow Diamond , the department was responsible for studying the diseases of living plants, the effects of parasites, and the study and testing of insecticides, fungicides, and fumigants.
Keywords: Agricultural chemicals; Employees; Chemical industry; Scientific apparatus and instruments; Dow Chemical Company; Corporations; Agricultural chemistry; Laboratories